Semi-empirical calculations of radiative decay rates in Mo II. A comparison between oscillator strength parametrization and core-polarization-corrected relativistic Hartree-Fock approaches. (September 2017) - Bouazza, Safa; Palmeri, Patrick; Quinet, Pascal
Highlights: Two different semi-empirical methods were used to study Mo II oscillator strengths. The agreement is excellent between these two approaches and also with experimental values. A complete list of 2243 transitions from depopulated 4d 4 5p and 4d 3 5s5p odd-parity levels have their oscillator strength and transition probability values computed for a first time. A survey of many extracted ion transition radial integral values shows clearly a real drop with filling nd-shells of the same principal quantum numbers for nd k (n + 1)s)-> nd k (n + 1)p transitions. Abstract: We present a semi-empirical determination of Mo II radiative parameters in a wide wavelength range 1716–8789 Å. Our fitting procedure to experimental oscillator strengths available in the literature permits us to provide reliable values for a large number of Mo II lines, predicting previously unmeasured oscillator strengths of lines involving 4d 4 5p and 4d 3 5s5p odd-parity configurations. The extracted transition radial integral values are compared with ab-initio calculations: on average they are 0.88 times the values obtained with the basic pseudo-relativistic Hartree Fock method and they agree well when core polarization effects are included. When making a survey of our present and previous studies and including also those given in the literature we observe as general trends a decreasing of transition radial integral values with filling nd shells of the same principal quantum numbers for n d k ( n + 1)s → n d k ( n + 1)p transitions.